The Relationship of Comorbid Overweight-Obesity With Cold Executive Functions, Verbal Short-Term Memory, and Learning in Attention Deficit Hyperactivity Disorder. Issue 11 (November 2021) - Guler, Hasan Ali; Turkoglu, Serhat
Abstract : Abstract: The aim of this study was to investigate the relationship between comorbid obesity/overweight and cold executive functions, verbal short-term memory, and learning in children with attention deficit and hyperactivity disorder (ADHD). Our study was conducted on 100 drug-naive participants, including 70 patients with ADHD and 30 healthy controls. In our study, patients diagnosed with ADHD were divided into two groups according to body mass index as above the 85th percentile and at or below the 85th percentile. Cold executive functions were evaluated by the Stroop Test (ST) and Cancellation Test (CT). Serial Digit Learning Test (SDLT) was administered to measure verbal short-term memory and learning capacity. To evaluate the severity of ADHD objectively, the parents completed the Conners' Parents Rating Scale–Revised Short Version (CPRS-RS). There was no statistically significant difference in ST, SDLT, CT scores, and CPRS-RS subscale scores between the two groups with ADHD. This study show that overweight/obesity comorbid with ADHD may not be associated with cold executive functions, verbal short-term memory, learning, or ADHD symptom severity.